Climate variability and recruitment success of European hake (Merluccius merluccius L.) in NW Africa - Meiners-Mandujano, César Gabriel; Fernández-Peralta, Lourdes; Torres-Cutillas, Pedro; Ramos, Ana (2006)
Recently it was stated a strong dependence of European hake abundance with climate variability in NW Africa. This relationship was explained by the North Atlantic Oscillation (NAO) driving the upwelling temporality and its geographic coverage, which could be responsible of changes in survival rate during early life stages of this species. Following this hypothesis, this work focuses on the relative importance of climate variability on recruitment dynamics of European hake. Interannual variability of recruitment success were analyzed through two types of time series: (i) from monthly and annual length distribution fishery data (1982-1999) of Spanish trawling fleet that worked under Spanish or European-Moroccan fishery agreements and (ii) recruits annual abundance from scientific Moroccan surveys (1982-2004). The time series were compared with the annual smoothed NAO index to evaluate the type of relationship, persistence and their relative contribution as a variation source of recruitment success. The recruitment to the fishery took place during all year with peaks in spring and summer, but the seasonal component was weak. The time series were in synchrony with NAO index of the previous year and showed strong positive correlation. The variation of recruitment success explained by NAO was 25 to 82 % depending on time series size. The main NAO effect in recruitment dynamics was the widening-contraction of Recruitment Window. During NAO+ phase several success cohorts were recruited by year, while in NAO- the success cohorts were scarce and weak. The climate signal in recruitment dynamics of European hake was robust, recurrent and persistent independently of fishing effort.